Assessment of the epidemiological effects of using of the pentavalent rotavirus vaccine at a low level of vaccination coverage of the target cohort - T. A. Kozhakhmetova; K. V. Kuleshov; D. H. Kjasova; T. A. Konovalova; N. V. Parkina; A. T. Podkolzin (Журнал инфектологии, 2019)
Background: Assessment of the informativeness of using various parameters characterizing the epidemic process during rotavirus infection to analyze the effects of the RotaTeq (MSD, USA) pentavalent rotavirus vaccine’s using at low (<20%) level of vaccination coverage of the target cohort. Materials and methods: Were analyzed the correlation links between the vaccination coverage rates and the number of reported cases of rotavirus infection, incidence rates, the number of rotavirus-positive laboratory tests and their shares among the examined children for the territories of Moscow and the Moscow Region in 2014-2018, using the database of the laboratory information system and data of the Federal statistical monitoring, Results: The presence of a strong reliable inverse correlation between the coverage of vaccination and the only of the analyzed indicators – the share of positive results of laboratory studies in the age group of children 6-24 months was revealed. There was a one and a half to two-fold decrease in the share of positive laboratory tests for rotavirus infection in the years of reaching 18–20% vaccination coverage. Conclusion: The obtained data indicate the high informative value of laboratory information system data and the perspective of their use for a comprehensive assessment of the activity of the epidemic process.